Vegetation Ecostructure in the Mejet Community Forest Conservation Block, North Lombok Regency - Wirebakti, Lalu Gede Galuh; Valentino, Niechi; Anwar, Hairil (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Mejet HKm Protection Block plays a crucial role as a water catchment area and supports the livelihoods of the surrounding community. This area serves as a water source for domestic needs, agricultural irrigation, and supports the growing ecotourism activities in the surrounding area. This study aimed to determine the ecostructure of plant vegetation in the Mejet Community Forest Protection Block, including species composition, horizontal and vertical structures, and the Importance Value Index (IVI), as well as the diversity, evenness, and richness indices of plant species. The research method used grid lines with a systematic sampling technique with random origins. Vegetation data were categorized based on the growth stage of seedlings, saplings, poles, and trees. The results showed that there were 95 plant species with Coffea sp. as the species with the largest number of individuals. The horizontal vegetation structure was dominated by small to medium diameter classes, while the vertical structure was dominated by low height classes, indicating that the vegetation regeneration process was still active. The highest IVI value at the seedling and sapling levels was held by Brownlowia peltata, at the pole level by Tabernaemontana, and at the tree level by Palaquium obtusifolium. The highest species diversity index value at the tree level was 3.69. The evenness and species richness indices across growth strata were also high, indicating a relatively even distribution of individuals across species and a stable forest ecosystem. Overall, the vegetation in the Mejet HKm Protection Block reflects a diverse, stable, and regenerative plant community, which supports the sustainable ecological function of the forest area.